Prevalence of anisometropia and influencing factors among school-age children in Nantong, China: a cross-sectional study - Zhou, Yue; Zhang, Xiao Fang; Chen, Xiao Juan; Wang, Min; Cai, Jian Ru; Xiong, Yao Jia; Song, Yu; Sun, Zhi Min (Frontiers in Public Health, 2023)
Objective: To investigate the prevalence of anisometropia and associated parameters among school-aged children in Nantong, China. Methods: This school-based, cross-sectional study examined students from primary schools, junior high schools, and senior high schools in an urban area of Nantong, China. Univariate and multivariate logistic regression analyses were used to investigate the specific correlations between anisometropia and related parameters. Non-cycloplegic autorefraction was assessed for each student. Anisometropia was defined as the spherical equivalent refraction (SE) difference ≥ 1.0 D between eyes. Results: A total of 9,501 participants were validated for analyses, of which 53.2% (n = 5,054) were male, and 46.8% (n = 4,447) were female. The mean of age was 13.32 ± 3.49 years, ranging from 7–19 years. The overall prevalence of anisometropia was 25.6%. Factors such as myopia, scoliosis screening positive, hyperopia, female sex, older age, and higher weight had a significantly higher risk of anisometropia (P < 0.05). Conclusions: There was a high prevalence of anisometropia in school-age children. Preventing myopia and controlling its progression may be the most important ways to reduce the prevalence of anisometropia. Correcting scoliosis may be an important factor in controlling the prevalence of anisometropia, and maintaining good reading and writing posture may be helpful in controlling the prevalence of anisometropia.